Evaluation of Asphalt Mixtures From the Correction of the Failure Area in the IDEAL Test - Oscar Javier REYES ORTIZ; Juan Sebastian USECHE-CASTELBLANCO; Marcela MEJIA (Engineering Transactions, 2021)
The IDEAL cracking test was developed in 2019 in the Texas A&M Transportation Institute as an alternative to evaluate the fracture tolerance of asphalt mixtures by the same indirect tensile strength test but with a different interpretation. In this methodology, the fracture area is described as a plane surface. However, the fracture of the asphalt mix is characterized by its irregularity and a non-uniform failure surface. For this reason, this work presents a model to determine the actual area of the failure for a set of asphalt mixtures with different characteristics using a 3D scanner. The main goal is to determine a possible correction factor of the actual fracture surface and observe the IDEAL test modification. This study shows that it is possible to standardize the correction factor for four of the five mixtures.